Application of Make A Match to Improve Students' Chemistry Learning Outcomes in Vocational Schools - Nobelia L. M. Siregar; Hartono Hartono; Dewi Kusmawaty (Institute of Multidisciplinary Research and Community Service, 2023)
Abstract: Application Make A Match to Improve Learning Outcomes Student Chemistry in SMK. In this research cooperative learning model type make a match applied. Cooperative learning type make a match is one of learning model enable students to study easier because the students will discuss one another, students are encouraged to have enthusiasm, active, and confidence. The goodness of this learning model are : (a) physically (cognitive aspect it will improve student’s learning activity; (b) this is an enjoyable that involve games learning model; (c) not only improve student’s comprehending on topic learned but also student’s learning interest; (d) student’s confidence to present their ideas will be trained effectively; (e) student’s discipline will be trained effectively. This is a classroom action research. The research conducted in grade X TITL 3 SMK Negeri 4 Palembang with 36 students. Research conducted in two cycles with some stages, they are : (a) planning; (b) action; (c) observation; (d) reflection. Based on the research result, in the first cycle percantage of students who pass the minumum standard (75 in scale of 100) are 41,67% and in the second cycle the percentage become 86,11%. There’s improvement in second cycle. Target percentage is 85%, therefore this classroom ation research is success improve student’s learning outcome and student’s learning interest.Keywords: make a match